HOMOGENOUS REGISTRY FIELDS WITH PROGRAMMABLE STRUCTURE - I. P. Kadiev; P. A. Kadiev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In article the new class of homogeneous environments called by authors “homogeneous register environments with programmable structure" which basic paradigm is the mathematical apparatus of expanded binary fields of E.Galua of GF (2m) is offered.